Mapping Groundwater Potential Zone Based on Remote Sensing and GIS Using Analytical Hierarchy Process (AHP) in Tana Righu, West Sumba, Indonesia - Arnoldus Nama; Welem M. W. L. Daga; Yacob Victor Hayer; Dedy Ardianto Fallo (JUTEKS : Jurnal Teknik Sipil, 2023)
This study aims to delineate groundwater potential zones in Tana Righu. Multiple thematic maps were prepared using RS and GIS techniques and was assigned suitable weights on the Saaty’s scale. The assigned weights of the thematic maps were then normalized using the AHP technique. Ultimately, these thematic maps were integrated with a weighted overlay technique in GIS. The results showed that about 42% of the study area has “moderate” potential; 35.86% of the study area has “high” potential; 28,82% of the study area has ”low” potential. 3.57.1% of the study area has “very high” potential; and 1.56.1% of the study area The “very low” potential. Overall, this study provides more efficient approach to mapping the potential groundwater availability. The results of this study are expected to assist in the planning, management and better utilization of groundwater resources.